2022
DOI: 10.3389/fneur.2022.741717
|View full text |Cite
|
Sign up to set email alerts
|

Moderate and severe TBI in children and adolescents: The effects of age, sex, and injury severity on patient outcome 6 months after injury

Abstract: The interaction of age, sex, and outcomes of children with head injury remains incompletely understood and these factors need rigorous evaluation in prognostic models for pediatric head injury. We leveraged our large institutional pediatric TBI population to evaluate age and sex along with a series of predictive factors used in the acute care of injury to describe the response and outcome of children and adolescents with moderate to severe injury. We hypothesized that younger age at injury and male sex would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Previous pediatric studies have investigated PLR using conventional pupillometry and brain injuries. Several studies have shown that abnormal or absent PLR during a PICU course is significantly correlated with increased mortality [25][26][27] and unfavorable PCPC outcomes [27]. The presence of PLR before initiating therapeutic hypothermia among children after cardiac arrest was significantly associated with favorable neurologic outcomes at the six-month follow-up [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous pediatric studies have investigated PLR using conventional pupillometry and brain injuries. Several studies have shown that abnormal or absent PLR during a PICU course is significantly correlated with increased mortality [25][26][27] and unfavorable PCPC outcomes [27]. The presence of PLR before initiating therapeutic hypothermia among children after cardiac arrest was significantly associated with favorable neurologic outcomes at the six-month follow-up [28].…”
Section: Discussionmentioning
confidence: 99%
“…These factors affect the sensitivity and plasticity of brain injury, as well as the capacity for repair and reorganization post-injury. Different individual-related factors may impact various cognitive domains differently, and there may be interactions between these factors, making the risk and degree of cognitive impairment more difficult to predict and assess ( Himanen et al, 2011 ; Skaansar et al, 2020 ; Gomez et al, 2021 ; Mollayeva et al, 2021 ; Izzy et al, 2022 ; Kennedy et al, 2022 ; Mair et al, 2022 ; Hume et al, 2023 ).…”
Section: Risk Factors Of Cognitive Impairment In Chinese Tbi Patients...mentioning
confidence: 99%
“…TBI is often classified as mild, moderate, or severe. Mild TBI accounts for nearly 70–90% of all reported TBIs, but severe TBI has the highest association with mortality ( Holm et al, 2005 ; Kennedy et al, 2022 ). Although only 11% of TBIs are moderate in nature, they account for longer lasting effects than mild TBI, such as cognitive and social deficits( Dewan et al, 2019 ).…”
Section: Neuroinflammation and Tbimentioning
confidence: 99%